Anthropogenic influence on recent circulation‐driven Antarctic sea ice changes. Issue 23 (15th December 2014) - Haumann, F. Alexander; Notz, Dirk; Schmidt, Hauke
Abstract: Observations reveal an increase of Antarctic sea ice over the past three decades, yet global climate models tend to simulate a sea ice decrease for that period. Here we combine observations with model experiments (MPI‐ESM) to investigate causes for this discrepancy and for the observed sea ice increase. Based on observations and atmospheric reanalysis, we show that on multidecadal time scales Antarctic sea ice changes are linked to intensified meridional winds that are caused by a zonally asymmetric lowering of the high‐latitude surface pressure. In our simulations, this surface pressure lowering is a response to a combination of anthropogenic stratospheric ozone depletion and greenhouse gas increase. Combining these two lines of argument, we infer a possible anthropogenic influence on the observed sea ice changes. However, similar to other models, MPI‐ESM simulates a surface‐pressure response that is rather zonally symmetric, which explains why the simulated sea ice response differs from observations. Key Points: Observed Antarctic sea ice trends could be caused by anthropogenic drivers A zonally asymmetric circulation change drives observed net sea ice increase A zonally too symmetric circulation change in models causes sea ice decrease